The Effect of Counseling Using E-Booklets on The Knowledge of Mothers with Infants Aged 0-6 Months about Exclusive Breastfeeding - Veraliza Magdalena; Wahyu Astuti; Aspia Lamana (MEDICA (International Medical Scientific Journal), 2025)
Globally, the rate of exclusive breastfeeding in the first six months is low. Exclusive breastfeeding is defined as feeding a baby breast milk from birth for six months, without adding or substituting any other food or drink (except medicine, vitamins, and minerals). Exclusive breastfeeding during the first six months of a baby's life is an important practice, but its coverage is still low in some regions. In West Kalimantan, exclusive breastfeeding coverage in 2023 reached 49.1%, while in Pontianak City it was only 38.7%, far below the national target of 80%. This study used a pre-experimental design with a one-group pretest-posttest approach to analyze the effect of health education through E-booklets on breastfeeding mothers' knowledge about exclusive breastfeeding. A total of 30 respondents, mothers with infants aged 0-6 months at PMB Marsini Karni, were selected using total sampling technique. Data were analyzed using the Wilcoxon test. The results showed a significant increase in knowledge after the intervention. Before the education was provided, the median knowledge score was 64, and after the E-booklet was provided, the median score increased to 86. Statistical testing yielded a p-value of 0.001 (< 0.05), indicating a significant improvement in breastfeeding mothers' knowledge following the intervention. In conclusion, health education delivered through E-booklets was effective in increasing breastfeeding mothers’ knowledge about exclusive breastfeeding.